A Review of the Importance of Maternal-fetal Attachment According to the Islamic Recommendations - Fatemeh Ghodrati; Marzieh Akbarzadeh (Journal of Midwifery & Reproductive Health, 2018)
Background & aim: Maternal-fetal attachment has an important effect on mother's identity as well as maternal and fetal health. Moreover, this concept is considered as a crucial issue for the improvement of children emotional development. Regarding the Islamic recommendations on maternal-fetal attachment and its correlation with maternal affection, this study was conducted to review the importance of maternal-fetal attachment according to the Islamic recommendations. Methods: This review was conducted on the religious texts, which covered the subject of interest and were published within 2000-2017. Various databases including Medline, PubMed, Google, IranMedex, SID, and Magiran as well as the websites of Muslim authorities (i.e., the section responding to religious questions) were searched. The searching was carried out using keywords as: “Islamic religious teachings”, “pregnant women and Fatwa of the Islamic jurists”, and “aspects of maternal fetal attachment in Islam”. Results: According to the results of the reviewed texts, the mutual readiness of mother and fetus leads to the improvement of their affection. The maternal factors affecting the maternal-neonatal attachment included personality traits, marriage, selection of partner, post-marriage issues, pregnancy, as well as physical and psychological characteristics. There were also some effective factors on the newborn’s innate readiness for the development of attachment, such as fetal appearance, family and social support, maternal nutrition during pregnancy, and neonatal mood. Conclusion: According to the Holy Quran versus and hadiths, maternal-fetal attachment and its promotion are affected by both maternal and fetal factors. Moreover, following the factors affecting attachment will lead to their role functioning. Therefore, it is intensively recommended to incorporate a glance of Islamic instruction into the pregnancy education to improve the maternal-fetal attachment.